2018
DOI: 10.1177/0271678x18800593
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA-126 in vascular cognitive impairment in mice

Abstract: Vascular dementia (VaD) affects cognition and memory. MicroRNA-126 (miR-126) is an angiogenic microRNA that regulates vascular function. In this study, we employ a multiple microinfarction (MMI) model to induce VaD in mice, and investigate VaD-induced cognitive dysfunction, white matter (WM) damage, glymphatic dysfunction and the role of miR-126 in mediating these effects. Male six-to eight-months old C57/BL6 mice (WT) were subject to MMI model, and cerebral blood flow (CBF), vessel patency, glymphatic functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 39 publications
4
56
0
Order By: Relevance
“…*P < 0.05, ** P < 0.01, NS P > 0.05, n = 4/group subdural cavity to the peripheral circulation was not completely ruled out in this work, the decreased drainage efficacy after cervical lymphatic vessel ligation strongly indicates that a direct pathway from the mLVs to the extracranial lymphatic system plays a key role in intracranial waste clearance. Because the lymphatic system is independent of the circulation, this new finding of an intracranial-extracranial lymphatic drainage pathway also provides a reasonable explanation for the lack of inflammatory reactions during clinical CSDH formation and atorvastatin-driven haematoma elimination [36,40].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…*P < 0.05, ** P < 0.01, NS P > 0.05, n = 4/group subdural cavity to the peripheral circulation was not completely ruled out in this work, the decreased drainage efficacy after cervical lymphatic vessel ligation strongly indicates that a direct pathway from the mLVs to the extracranial lymphatic system plays a key role in intracranial waste clearance. Because the lymphatic system is independent of the circulation, this new finding of an intracranial-extracranial lymphatic drainage pathway also provides a reasonable explanation for the lack of inflammatory reactions during clinical CSDH formation and atorvastatin-driven haematoma elimination [36,40].…”
Section: Discussionmentioning
confidence: 78%
“…CSDH is predicted to be one of the most common neurosurgical diseases, especially in individuals over 70 years old [21,27,28]. It has been demonstrated that CSDH can be absorbed spontaneously and that atorvastatin can promote this process [35,40]. Despite the presence of multitudinous and dense inflammatory cytokines in CSDHs, only a few patients have demonstrated systemic inflammatory responses that include fever and increased white blood cell counts during the process of haematoma absorption [11,19,26], and most CSDH patients present with mild neurological symptoms [17].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have found that mice subjected to MMI have significantly decreased miR-126 expression which may play a key role in mediating cognitive impairment after MMI (Yu et al, 2019). Also, mice with endothelial miR-126 knockdown exhibited significant cognitive dysfunction, reduced CBF, WM rarefaction including decreased myelin and axon density, increased inflammation and glial activation, and significant glymphatic dysfunction (Yu et al, 2019). We have previously demonstrated that HUCBC treatment increases miR-126 expression and improves functional outcome, promotes WM remodeling, and reduces inflammation after stroke in diabetic mice (Chen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Also, HUCBC transplantation is safe and well-tolerated in human patients with AD in the Phase 1 clinical trial (Kim et al, 2015). In our previous study, we reported that mice subjected to MMI have significantly decreased miR-126 expression, and mice with endothelial miR-126 knockdown exhibit significant cognitive impairment, WM injury, and glymphatic dysfunction (Yu et al, 2019). MiRs, and particularly miR-126, are emerging as key players in the pathogenesis of vascular damage (Zampetaki et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While the angiogenic miRNA, miR‐126, is a regulator of vascular function, its serological level was declined following VD. Downregulation of miR‐126 in the VD mice model coincides with higher inflammation, glymphatic and water channel dysfunction, lower myelin and axon density, and worsened cognitive function and cerebral blood flow (Yu et al, 2019). Ragusa et al (2016) revealed a reduction in the levels of miR‐10b‐3p, miR29a‐3p, and miR‐130b‐3p in VD sufferers compared to control individuals.…”
Section: Neurological Disorders Associated With Cognitive Impairmentmentioning
confidence: 99%